Analisis Kemampuan Multirepresentasi Siswa dalam Menyelesaikan Soal Pesawat Sederhana Ditinjau dari Aspek Adversity Quotient - Hotimah, Khusnul; Hadi, Wiwin Puspita; Ahied, Mochammad; Qomaria, Nur; Sutarja, Maria Chandra (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
Multi-representation ability is one of the important skills to be developed. One of them is because it can play a role in helping students master the material being taught. In science subjects, one of the materials that uses quite diverse forms of representation is simple planes. This shows that there is a possibility that students' multi-representation abilities will affect students' understanding of the material. In addition, another factor that can influence is the adversity quotient of students. Therefore, this research was conducted to determine the students' multi-representation ability on simple plane material in terms of Adversity Quotient Aspects. The research method used is a mixed method with a sequential explanatory design. The subjects of this study were students of class VIII G UPTD SMP Negeri 2 Bangkalan with a total of 30 students. The research instrument used was a multi-representation ability test and interview guidelines. The results of this study are the high category of multi-representation abilities consisting of 4 students, the medium category consisting of 22 students, and the low category consisting of 4 students with an average test score of 58.33. The results of the interview show that students' multi-representation abilities and understanding of simple plane materials support and influence each other. Students with multi-representation abilities and good understanding of the material can easily understand the questions given and can also give correct answers, thus obtaining high test scores. owever, the adversity quotient is not always directly proportional to student test results.